First-line contact aspiration versus first-line stent retriever for acute posterior circulation strokes: an updated meta-analysis. (25th May 2021) - Ye, Gengfan; Wen, Xuebin; Wang, Hongcai; Sun, Chengfeng; Pan, Zhihao; Chen, Maosong; Wang, Boding; Li, Zhenqiang
Abstract : Background: Both stent retriever (SR) and contact aspiration (CA) are widely used as first-line strategies for acute posterior circulation strokes (PCS). However, it is still unclear how CA and SR compare as the first-line treatment of acute PCS. Several new studies have been published recently, so we aimed to perform an updated meta-analysis. Methods: The meta-analysis was conducted according to the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analysis) statement. Random-effects models were performed to pool the outcomes and the value of I 2 was calculated to assess the heterogeneity. Results: Ten observational studies with 1189 patients were included, among whom 492 received first-line CA and 697 received first-line SR. The pooled results revealed that first-line CA could achieve a significantly higher proportion of modified Thrombolysis In Cerebral Infarction (mTICI) 2b/3 (OR 1.90, 95% CI 1.33 to 2.71, I 2 =0%), mTICI 3 (OR 1.95, 95% CI 1.15 to 3.31, I 2 =59.6%), first-pass effect (OR 2.91, 95% CI 1.51 to 5.58, I 2 =0%), lower incidence of new-territory embolic events (OR 0.20, 95% CI 0.05 to 0.83, I 2 =0%), and shorter procedure time (mean difference −29.4 min, 95% CI −46.8 to −12.0 min, I 2 =62.8%) compared with first-line SR. At 90-day follow-up, patients subjected to first-line CA showed a higher functional independence (modified Rankin Scale score 0–2; OR 1.38, 95% CI 1.01 to 1.87, I 2 =23.5%) and a lower mortality (OR 0.71, 95% CI 0.50 to 1.00, p=0.050, I 2 =0%) than those subjected to first-line SR. Conclusions: This meta-analysis suggests that the first-line CA strategy could achieve better recanalization and clinical outcomes for acute PCS than first-line SR. Limited by the quality of included studies, this conclusion should be drawn with caution.